How I met my soulmate. 1 - Anashin, 1992- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2023)
From the creator of Waiting for Spring comes a new college romance that meditates on just what destiny means, and whether "the one" is really out there. A fresh and stylish spin on shojo manga! Yuuki is a 20-year-old college sophomore who has wished for one thing since moving to Tokyo: to find her soulmate. Growing a bit desperate after a long drought, she goes along with a friend to a club for the first time. Her friend thrives, but it's chaotic and loud...just not Yuuki's scene. Just when Yuuki begins to despair that she'll ever find a real, adult relationship, she meets Iori, a man with bleached hair and a slightly scary demeanor...but first impressions don't always tell the whole story. Could destiny still have more cards to play?